Pemberdayaan Berbasis Innovative Community-Centered Dengue-Ecosystem Management untuk Menurunkan IR DBD - Sukendra, Dyah Mahendrasari; Indrawati, Fitri; Hermawati, Bertakalswa; Santik, Yunita Dyah Puspita; Maharhani, Arvia Dhitya; Fitri, Anisa (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2021)
Based on data from the Central Java Province Health Profile in 2019, it was stated that the IR of Central Java's DHF was 25.9 per 100,000 population with a CFR of 1.5%. Karanganyar Regency is recorded to have the highest IR DBD in Central Java, namely 94.5 per 100,000 population, and the last 3 years, DHF cases have jumped to 30% compared to the previous year which only occurred 76 cases. This study aims to determine differences in the level of knowledge of PKK mothers regarding dengue hemorrhagic fever and its prevention practices in RT 2 and RT 3 Sabrang Kulon sub Village of Matesih Village through innovative community-centered dengue-ecosystem management based empowerment. This research was conducted in August and September 2020. This study used an experimental design using a one-group before-after study design and instruments using a questionnaire. There was no difference in the knowledge scores of PKK mothers about DHF before and after being given training (p = 0.102). In conclusion, there is no difference in the knowledge of PKK RT 2 and RT 3 Sabrang Kulon Village women regarding dengue hemorrhagic fever and its prevention practices before and after counseling. Keywords: Knowledge, Community, Dengue Haemmoragic Fever, Prevention